Extended calibration of cold-water coral Ba/Ca using multiple genera and co-located measurements of dissolved barium concentration - Spooner, Peter; Robinson, Laura F.; Hemsing, Freya; Morris, Paul; Stewart, Joseph A. (Chemical geology, 2018)
Biological productivity and ocean circulation are both important oceanographic variables that control the distribution of dissolved barium in the ocean interior ([Ba]sw). The ability to accurately reconstruct [Ba]sw will provide key constraints on these processes in the past. The geochemistry of cold-water corals has the potential to unlock paleoceanographic records at spatial and temporal resolutions not available using other sedimentary archives. Previous studies have suggested that the Ba/Ca ratio of coral skeletons is linearly related to [Ba]sw. However, these efforts have used a limited number of species, sparse global seawater databases, or have not explicitly measured the Ba/Ca ratio. Here we investigate the Ba/Ca ratio in a well-constrained set of cold-water scleractinian (aragonitic) corals as a proxy for [Ba]sw, using 58 specimens from 7 coral genera along with co-located measurements of [Ba]sw. We find that traditional chemical cleaning procedures do not significantly affect the Ba/Ca ratio of cold-water coral skeletons, allowing rapid sample throughput. We also determine that intra-sample variation in Ba/Ca ratios can be reduced by using larger sample sizes (e.g. 20mg). By combining our results with existing data, we find that cold-water coral Ba/Ca is linearly related to [Ba]sw according to the relationship: Ba/Ca μmol/mol=[0.15±0.02] [Basw nmol/kg]+[2.5±1.4], (R2=0.7). We observe no species-specific ‘vital effects’ in cold-water coral Ba/Ca ratios, but site-specific effects could be a factor. Nevertheless, our results highlight the potential of Ba/Ca in cold-water corals to reconstruct biological and physical changes in the ocean interior.
Gesehen am 02.04.2020